A polymorphism in human CD1A is associated with susceptibility to tuberculosis - Seshadri, C; Thuong, N; Yen, N; Bang, N; Chau, T; Thwaites, G; Dunstan, S; Hawn, T (Nature Publishing Group, 2014)
CD1 proteins are antigen-presenting molecules that evolved to present lipids rather than peptides to T cells. However, unlike major histocompatibility complex genes, CD1 genes show low rates of polymorphism and have not been clearly associated with human disease. We report that an intronic polymorphism in CD1A (rs411089) is associated with susceptibility to tuberculosis in two cohorts of Vietnamese adults (combined cohort odds ratio 1.78; 95% confidence interval: 1.24-2.57; P=0.001). These data strengthen the hypothesis that CD1A-mediated lipid antigen presentation is important for controlling tuberculosis in humans. Copyright © 2014 Macmillan Publishers Limited.